2021
DOI: 10.3390/genes12101575
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of CDH1 Is Altered after HOXB7-Silencing in MDA-MB-468 Triple-Negative Breast Cancer Cells

Abstract: HOXB7 is often overexpressed in breast cancer cells and found to relate to poor prognosis. The search for the HOXB7 targets, as a transcription factor, has led to molecules involved in regulating cell proliferation, migration, invasion, and processes such as angiogenesis and therapy resistance. However, the specific targets affected by the deregulation of HOXB7 in breast cancer remain largely unknown in most molecular sub-types, such as triple-negative breast cancers (TNBC). To unveil the molecular basis behin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Hyman team detected HOXB7 amplification in 10% of the 363 cases of breast cancer and found a direct correlation between amplification and poor prognosis 40 . Additionally, studies have reported that inhibiting HOXB7 expression in MDA‐MB‐468 triple‐negative breast cancer can regulate the expression of CDH1 through epigenetic mechanisms, thereby modulating the metastatic potential of breast cancer 27 . After correlation analysis, MIR143HG was found to be negatively related to HOXB7 (Figure 3A).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The Hyman team detected HOXB7 amplification in 10% of the 363 cases of breast cancer and found a direct correlation between amplification and poor prognosis 40 . Additionally, studies have reported that inhibiting HOXB7 expression in MDA‐MB‐468 triple‐negative breast cancer can regulate the expression of CDH1 through epigenetic mechanisms, thereby modulating the metastatic potential of breast cancer 27 . After correlation analysis, MIR143HG was found to be negatively related to HOXB7 (Figure 3A).…”
Section: Resultsmentioning
confidence: 88%
“…40 Additionally, studies have reported that inhibiting HOXB7 expression in MDA-MB-468 triple-negative breast cancer can regulate the expression of CDH1 through epigenetic mechanisms, thereby modulating the metastatic potential of breast cancer. 27 After correlation analysis, MIR143HG was found to be negatively related to HOXB7 (Figure 3A). As shown in Figure 3B, HOXB7 was highly expressed in colon cancer-related RNAseq data in the TCGA database.…”
Section: Hoxb7 Is Upregulated In Colon Cancer and Negatively Regulate...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, HOXB7 is highly expressed in breast cancer, ovarian cancer, and melanoma samples. [42][43][44][45] STC2 is highly expressed in rectal cancer and colon cancer. [46,47] TMEM158 is upregulated in laryngeal cancer, glioblastoma, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%